Analyzing Troubleshooting of BTS Transmit Power and 4G LTE Coverage Area via VSWR Value Measurement - Nadila Khairanisa; Siska Aulia; Sri Yusnita; Yulindon Yulindon (Andalas Journal of Electrical and Electronic Engineering Technology, 2023)
The Voltage Standing Wave Ratio (VSWR) serves as a comparative measure between transmitter and receiver voltages, impacting site transmit power. VSWR values at a Radio Base Station (RBS) are evident in feeder cable losses, jumpers, combiners, and radio antenna losses. This study aims to assess the impact of poor VSWR values on BTS transmit power and perform troubleshooting analysis on 4G signal quality and Coverage Area. The study commenced with a literature review and VSWR measurements in the Gurun Laweh Aia Pacah region. The process involved identifying VSWR issues at the BTS site, conducting a Drive Test using pocket Tems, and troubleshooting the VSWR problem. Drive Test findings encompassed areas with weak signals, BTS site data, and problematic spots. The analysis utilized applications like Tems Discovery and MapInfo Pro. Results along the Gurun Laweh Aia Pacah road showed signal strength affected by a high VSWR value of 1.6. RSRP data rated 50% in the good category, SINR at 31% in the good category, and throughput at 5% in the good category. Elevated VSWR values diminish signal range, subsequently impacting traffic metrics. Immediate VSWR troubleshooting becomes imperative; low VSWR promotes higher transmit power efficiency, while normal VSWR ensures optimal transmit power efficiency.